A Estação Paleolítica do Cerro (Vila Nova de Gaia, Noroeste de Portugal): caracterização preliminar dos utensílios com configuração bifacial - Rodrigues, Sérgio Monteiro (2014)
The Palaeolithic site of Cerro was discovered in 1988. Between 1989 and 1992 three excavation seasons were carried out, which allowed collecting an important set of macrolithic stone tools most of them made of quartzite pebbles, possibly dating from the Lower Palaeolithic. From a geoarchaeological point of view, these stone tools were associated with colluvial deposits which overlay a marine formation c. 22 m a.s.l. The study of the bifacial shaped tools (including the parcial bifacial shaped and the unifacial tools) allowed the identification of two chaînes operatoires, basically expedite, oriented towards the production of pointed tools. These chaînes operatoires do not seem to be linked to morphological options but instead they may be a response to the constraints imposed by the volumetry of the blanks, possibly adapting them to distinct funcionalities.